HUBUNGAN ANTARA KOMUNIKASI EFEKTIF TENTANG SEKSUALITAS DALAM KELUARGA DENGAN SIKAP REMAJA AWAL TERHADAP PERGAULAN BEBAS ANTAR LAWAN JENIS - Titi Prihartini; Sartini Nuryoto; Tina Afiatin (Faculty of Psychology, Universitas Gadjah Mada, 2002)
This research was intended to discover the correlation relationship between the effective communications about sexuality in family on early adolescents’ attitude toward free socialization among youths of different sexes. The subjects of the research were 370 Junior High School students that consisted of 185 female students and 185 male students from SLTP PIRI I Yogyakarta and SLTPN 5 Depok Sleman. Three psychological scales made by the researcher were used to obtain the data. The first psychological scale was the communications about sexuality in family for the early female adolescents and it consisted of 23 items. The second psychological scale was the communications about sexuality in family for the early male adolescents and it also consisted of 23 items. The third psychological scale was the attitude toward free socialization among youths of different sexes and it consisted of 66 items. Data analysis by Pearson product moment analysis shows that the correlation relationship between the effective communications about sexuality in family and early adolescents’ attitude toward free socialization among youths of different sexes was significantly positive for both female and male students (rxy1 =0,201 ; p= 0,003 and rxy2 =0,147 ; p= 0,023 p ′ 0,05). The effective contribution given by the effective communications about sexuality in family on early adolescents’ attitude toward free socialization among youths of different sexes was 4% for female students and 2,2% for male students. Data analysis by applying the t – test analysis shows that there was a significant difference between female and male students’ attitude toward free socialization among youths of different sexes ( X L = 177,88 ∃ X P = 159,12; t = - 6,4 ; p = 0,000, p ′ 0,01). It means that the attitude of early male adolescents toward free socialization among youths of different sexes is higher than early female adolescents. Keywords: effective communications about sexuality in family, early adolescent,free socialization among youths of different sexes